Factors affecting saving in Sudan during the period 2008-2018 - Alkhabir, Minas Abdelrahman Ali (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to show the factors affecting saving in Sudan during the period 2008- 2018, The study used the historical method and the descriptive and analytical method. The most important results of the study were: that the disposable income was characterized by fluctuation between increase and decrease throughout the study period, affecting the marginal propensity to consume and save, but its effect was greater in double the marginal propensity to save as it did not exceed 0.39 compared to the marginal propensity to consume 0.60, The Sudanese economy suffered from a deficit in the general budget as a result of the increase in current expenditures over current revenues, and to finance this deficit, countries resorted the policy of inflationary financing, The study recommended the need to work on increasing the returns of saving deposit, in order to weaken the forces of consumption and reduce the growth rate of aggregate demand, following an economic reform plan that achieves financial stability and creates real investment opportunities that provide new job opportunities that lead to increased savings.